Mozambique's Cabo Delgado conflict : international humanitarian law and regional security - Svicevic, Marko; Bradley, Martha M. (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2024)
"This book uses a multidisciplinary approach to examine the ongoing conflict in Mozambique's Cabo Delgado province, which has killed thousands and displaced a million people since 2017. The book investigates how the conflict developed, the regional and international responses, and its wider implications. From a broad range of African perspectives, the book addresses issues related to the conflict including international humanitarian law, regional security, and terrorism. Part one assesses the regional security concerns of the conflict, the success of cross-border counter terrorism operations and its implications for the southern African region. Part two focuses on the conflict in relation to international humanitarian law. It discusses the Islamic State presence in the region, the trajectory and issues pertaining to sexual and gender-based violence, and the relationship between the conflict and the environment. Finally, part three examines regional and continental responses to the conflict; from the military intervention by the Southern African Development Community and Rwanda, to the perceived inaction of the African Union. The first comprehensive analysis of the conflict in Cabo Delgado, this book will be of interest to scholars and practitioners of international humanitarian law, security, African politics, war and conflict studies, terrorism and human rights"--
Introduction / Egna Sidumo, Marko Svicevic and Martha M Bradley -- Part I: Regional Security Dimensions -- Tanzania and Mozambique: Cooperation to Counteract a Cross-Border Islamist Insurgency / Eric Kabendera -- South Africa's Security Concerns in Mozambique and the Growing Threat of Domestic Terrorism / André Smit -- Armed Conflict, Climate Change and the Preparedness of International Law Through the Lens of Mozambique / Jessie Phyffer -- The Relationship Between Ansar al-Sunna in Mozambique and the Islamic State: A Transactional Alliance? / Aniel de Beer -- Part II: International Humanitarian Law Perspectives -- The Law of Armed Conflict and the Classification of the Situation in Cabo Delgado as a Non-International Armed Conflict / Najimdeen Bakarae and Ayodele Odjedokun -- Ansar al-Sunna (IS-affiliates) Engaging in a Mosaic of Violence in Mozambique: Terrorist, Rebels, or Both -- Legal Implications and Challenges / Gus Waschefort, Jessie Phyffer and Martha M. Bradley -- Sexual and Gender-Based Violence in Cabo Delgado: Implications for International Humanitarian Law and International Criminal Law / Emmah Lubaale and Brenda Akia -- Towards the Protection of the Environment in Cabo-Delgado: Looking Beyond the Existing Legal Framework and Engaging Ansar al-Sunna / Quillene M Vertue -- The Conflict in Cabo Delgado and the Relationship Between International Disaster Response Law and International Humanitarian Law Treaties / Jeanique Pretorius -- Covid-19 and its Implications on the Law of Non-International Armed Conflict: The Case of Mozambique / Annelize McKay, Chazanne Grobler and Martha M Bradley -- Part III: Regional and Continental Responses to the Conflict -- The Potential for Rights-Based Third-Generation Disarmament, Demobilisation, and Reintegration Programmes in Cabo Delgado / Josephat M Kilonzo -- The Use of Private Military Companies to Counter the Insurgency in Northern Mozambique / Hennie Strydom -- The SADC Mission in Mozambique: Contextualising the Historical Role of SADC Military Operations under International Law / Marko Svicevic -- The Military Intervention Against Ansar Al-Sunna in Cabo Delgado: A Primer on the Law on the Prohibition on the Use of Force and Applicable Exceptions / Dire Tladi -- Revisiting the African Union's Right to Intervene (Militarily) 20 Years on and the Conflict in Mozambique: A Missed Opportunity? / Ntombizozuko Dyani-Mhango.
Keywords: Humanitarian law -- Mozambique; Conflict management -- Mozambique -- Cabo Delgado; Security, International -- Africa, Sub-Saharan.; Terrorism -- Africa, Sub-Saharan -- Law and elgislation; Terrorism -- Africa, Sub-Saharan -- Prevention; POLITICAL SCIENCE / Political Freedom & Security / Terrorism; POLITICAL SCIENCE / Political Freedom & Security / International Security; LAW / International